Função exponencial e seu ensino através da resolução de problemas - Martinez, Daniela Alves [UNESP] (2015)
This work aims to present a proposal on how to teach the concepts related to Exponential Function through the Methodology of Resolution of Problems. In this regard, we sustain us on Polya and Onuchic theory and suggest two problems. In one of them is introduced the use of software Geogebra. Those exemplify how to apply the methodology of Resolution of Problems in the teaching of mathematic. The formalization of the boarded content in the problems are presented in this work, as well the results of application of the proposal for the first High School step